Étude de la déminéralisation des eaux souterraines par osmose inverse dans le sud est Algérien – cas de la station d’El Meghaier- - دقعة, علي; ترشة, حسين (university of Eloued جامعة الوادي, 2019)
The quality of the drinking water distributed to the consumer depends on the quality of the surface water or groundwater from which it is drawn and the treatments carried out after it has been drawn. In the oued righ region, drinking waters extracted from groundwater, its quality is generally salty, slighty brackish and poor to poor. In addition toits unpleasant quality, this water has a negative impact on the health of consumers. This alarm situation is at the origin of the construction of a demineralization station by Reverse Osmosis process in this region to obtain good quality water with low salinity, and a neutral pH and the refore fresh and pleasant water. نوعية مياه الشرب الموزعة على المستهلك تتعلق بنوعية المياه السطحية أو المياه الجوفية التي يتم أخذ منها والمعالجة التي تتم بعد أخذ العينات. في منطقة واد ريغ، يتم الحصول على مياه الشرب من المياه الجوفية ، ونوعيتها مالحة بشكل عام هذه المياه بالإضافة إلى جودتها غير محبوبة ، لها تأثير سلبي على صحة المستهلكين. هذا الموقف المثير للقلق هو في أصل في إنجاز محطة تحلية بعملية التناضح العكسي في هذه المنطقة للحصول على مياه ذات نوعية جيدة مع انخفاض الملوحة ، ودرجة الحموضة محايدة وبالتالي المياه العذبة.
مذكرة ماستر تخصص في منشئات الري
Keywords: Oued righ, salinity, freshness, Water, Demineralization, Reverse Osmosis.; وادي ريغ ، الملوحة ،العذبة ، الماء ، إزالة المعادن ، التناضح العكسي.